La réglementation : la pointe de l’Iceberg - Moreau, Rémi; Dumais, Christian N. (Assurances, 1983)
The following article written by lawyers Rémi Moreau and Christian N. Dumais describes various problems caused by regulations, which are growing more complex and wide-sweeping. This article is of particular interest as it deals with certain aspects which are to be studied by a government Commission.